Cracking and Photo-Oxidation of Polyoxymethylene Degraded in Terrestrial and Simulated Marine Environments - Tang, Chih-Cheng; Chen, Ying-Ting; Zhang, Yi-Ming; Chen, Huey-Ing; Brimblecombe, Peter; Lee, Chon-Lin (Frontiers in Marine Science, 2022)
Marine plastic debris is an environmental problem, and its degradation into microplastics (1-5000 μm) introduces them into the food chain. In this study, small polyoxymethylene (global production ~3000 Tg per year) pellets were exposed in terrestrial and simulated marine environments to heat and light, resulting in cracking during decay with increasing IR absorption (OH-bonds). Furthermore, sunlight over three years reduced pellet mass and diameter (~10% and ~40%), initially yielding 100-300 μm fragments. Changes under UV irradiation were smaller as it could not penetrate into particle interiors. Characteristic spacing of surface striations (100-300 µm) initiated radial cracks to pellet interiors, and breakdown ultimately meant 95% of particles were <300 µm, which are potentially incorporated in marine turbidites.